New electron-accepting pi-conjugated polyquinoxalines with fluorene unit: synthesis and light-emitting properties - Jung, SH; Suh, DH; Cho, HN (SPRINGER-VERLAG, 2003)
New fluorene-linked pi-conjugated polyquinoxaline PFQx I and PFQx II have been synthesized and characterized. The PFQx polymers are prepared by the polycondensation of the 2,7-bis(phenyloxoacetyl)-9,9'-di-n-hexylfluorene or 2,7-bis(4-benzil)-9,9'-di-n-hexylfluorene and 3,3'-diaminobenzidine leading to the PFQx I and PFQx II. The polycondensation is usually carried out in m-Cresol. These polymers possess relatively good solubility and thermal stability. The resulting polymers exhibit a UV-visible absorption band in the range of 397-407 nm in both chloroform solution and the film state. Upon photo-excitation around the absorption maximum wavelength, their PL spectra show a maximum peaks around at 447-467 nm. Multilayered light-emitting diode with the device structure of ITO/PEDOT/PFQx I /PVK blend(2:8)/LiF/AI gives a highest EL peak in the blue region of 460 nm. J-V curve shows a turn-on voltage of 13 V.
Keywords: POLYMER; THIOPHENE; DIODES; BLUE